2017
DOI: 10.1007/s12041-017-0756-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite markers in Garcinia gummi-gutta by next-generation sequencing and cross-species amplification

Abstract: Garcinia gummi-gutta (L.) Roxb. (Clusiaceae) is an endemic, semidomesticated, fruit-yielding tree species distributed in the Western Ghats of India and Sri Lanka. Various bioactive phytochemicals, such as garcinol, benzophenones and xanthones are isolated from G. gummi-gutta and have shown antibacterial, antiviral and antioxidant activities. We sequenced the total genomic DNA using Illumina Hiseq 2000 platform and examined 241,141,804 bp high quality data, assembled into 773,889 contigs. In these contigs, 27,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…However, it is unknown if selection is involved in the distribution of SSR types in genomic DNA (Celik et al, 2014). A similar trend was observed in other Garcinia species, G. indica (Ravishankar et al, 2021) and G. gummigutta (Ravishankar et al, 2017).…”
Section: G Indica G Gummiguttasupporting
confidence: 53%
“…However, it is unknown if selection is involved in the distribution of SSR types in genomic DNA (Celik et al, 2014). A similar trend was observed in other Garcinia species, G. indica (Ravishankar et al, 2021) and G. gummigutta (Ravishankar et al, 2017).…”
Section: G Indica G Gummiguttasupporting
confidence: 53%
“…[25] High variability among these quantitative characteristics strengthens the economic importance. [26] Likewise, in the present study twelve quantitative morphological markers were observed to estimate phenotypic diversity.N. sativa plant usually exhibited mixed (self / cross) pollination types but it is predicted that cross pollination may prove more fruitful with reference to genetic variation.…”
Section: Petal Colorsupporting
confidence: 52%
“…In cross species amplification, out of 48 SSR primers, 6 amplified in G. morella , accounting 12.5 per cent transferability and 9 amplified in G. gummigutta accounting 18.8 percent transferability (ESM2). This relatively low cross-species transferability compar ed to what has been observed in G. gummigutta species (Ravishankar et al, 2017).…”
Section: Short Communicationmentioning
confidence: 50%